Class preference and its relationship to increasing rates of aggressive behavior in secondary school students A field study on pupils of some secondary education institutions in the province of Jijel – Algeria - Bouab, Redouane; Kias , Abd Rachid (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2021)
The phenomenon of violence in educational and educational institutions is spreading in all its forms and forms in secondary education institutions on the grounds that the pupils belong to a sensitive age stage (adolescence) in which they seek to prove themselves and personality before others, rejecting all manifestations of neglect and marginalization, isolation, miniaturization and humiliation Preference and discrimination between them within the classroom and school, which may contribute to raising the rates of violent and aggressive behavior within this institutional and educational campus, and we aimed from this study to know the effects of classroom preference practiced by teachers on the rates of violence and abnormal behaviors within educational institutions In the secondary stage, where we are witnessing at the present time teachers neglecting some students and preferring others, and this may be due to several factors such as the economic level of the student’s family, his social status, kinship relationship, educational level, ... etc. and other factors that affect the professor’s relationship With his student, which inevitably creates abnormal and violent behaviors in the classroom playground, especially the school center in general, as well as negatively affecting the goals of the pedagogy. There is a relationship between class preference and the increase in the rates of aggressive behavior among secondary school students, and this relationship is a direct relationship. The more teachers increase the indicators of discrimination between students, the more rates they practice aggressive behaviors. And violent.